Indonesian Labour Migration: Identifying the Women - Sylvia Yazid (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2015)
This paper is concerned with two main issues, Indonesian women workingabroad in the informal sector, mostly as domestic workers and the potentialsof other women stakeholders in addressing issues faced by women migrantworkers. This paper is written based on the assumption that an identificationof potential women at various levels and institutions may contribute to thesearch for solutions for the problems faced by the women migrant workersand that women should be seen as active actors that may contribute to theproblem solving. The identification in this paper has been able to identify theexistence of a number of prominent women migrant workers advocates, arguefor their existence in various parts within the labour migration system toguarantee a protected migration for women labour, and suggest for thewidening of the scope and activism of these women migrant workersadvocates, in line with their movements across institutions.